Use of Redox Reactions for Estimation of Carvedilol - Srinivas, L.D.; Prasad Rao, K.V.S.; Sastry, B.S. (Asian Journal of Chemistry, 2016)
Simple and sensitive indirect spectrophotometric methods (M1 and M1) for the assay of Carvedilol in dosage forms based on their reactivity with N-bromo succinimide have been described. These methods involve the oxidation of drug with excess of N-bromo succinimide and estimating the unreacted N-bromo succinimide either with celestine blue (M1) or p-N-methyl amino phenol sulfate-sulfanilamide (M2). The results obtained are reproducible and are statistically validated.